Development and evaluation of biodegradable polymeric nanoparticles for the effective delivery of quercetin using a quality by design approach. Issue 2 (May 2015) - Dinesh Kumar, V.; Verma, Priya Ranjan Prasad; Singh, Sandeep Kumar
Abstract The aim of the present work is to develop biodegradable polymeric nanoparticles based oral drug delivery for encapsulation and controlled release of polyphenolic flavonoid (quercetin). The quercetin loaded poly (ɛ caprolactone) nanoparticles were prepared by nano-precipitation method using 32 factorial designs. The results of optimized formulations OPF1, OPF2 and OPF3 showed particle size of 215.9 ± 2.9, 228.6 ± 2.7, 253.4 ± 3.3 nm, the entrapment efficiency of 66.32 ± 0.4, 67.82 ± 0.7, 69.33 ± 1.0%, and drug release at 48 h of 66.05 ± 1.41, 64.12 ± 0.30, 62.82 ± 0.85%, respectively. SEM and AFM images represent spherical and smooth surface of nanoparticles. The results suggest that optimized formulations could promote the control release, and improves the physical stability of quercetin. In conclusion, polymeric nanoparticles could be a promising carrier for oral delivery of quercetin.